2017
DOI: 10.2136/vzj2016.08.0072
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Modeling of Soil Hydraulic Properties in a Two‐Layer System and Comparisons with Measured Soil Conditions

Abstract: Core Ideas Soil hydraulic properties were inverse modeled to in situ soil water content. The most appropriate soil property depths were identified. Best‐fit soil parameter depths compared well with characterized soil stratigraphy. Site‐specific monitoring and subsurface boundary conditions improved performance. Modeling of spatial and vertical variability in soil hydraulic properties is a pervasive dilemma in computational hydrology. In an effort to provide guidance in inverse modeling of soil hydraulic prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
0
6
0
1
Order By: Relevance
“…As the C horizon also differs in hydraulic properties, the soil profile storage capacity is affected as well, decreasing with solum thickness due to reduced soil water retention capacities. As found by Thomas et al (2017), variations in the thickness of the subsurface horizons could largely influence soil moisture dynamics and the water balance and also present challenges in property estimations and vadose zone modeling.…”
Section: Sensitivity Analysis: C Horizon Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…As the C horizon also differs in hydraulic properties, the soil profile storage capacity is affected as well, decreasing with solum thickness due to reduced soil water retention capacities. As found by Thomas et al (2017), variations in the thickness of the subsurface horizons could largely influence soil moisture dynamics and the water balance and also present challenges in property estimations and vadose zone modeling.…”
Section: Sensitivity Analysis: C Horizon Propertiesmentioning
confidence: 99%
“…Pennock et al, 2014). Thomas et al (2017) argued that soil stratigraphy (i.e., thickness of the subsurface horizons) could influence soil moisture dynamics.…”
mentioning
confidence: 99%
“…The soil can be represented as (i) a single layer (Jhorar et al 2002), with the estimated soil hydraulic properties thus assumed to represent those of multiple soil horizons, or (ii) multiple layers, which increases the number of parameters to be estimated (e.g., each layer's thickness and water contents at FC and PWP) (Seki et al 2015). Some authors showed that, regardless of model complexity, using multiple layers provides better performance than a single homogenous layer, except for soils with low heterogeneity (Schneider et al 2013;Thomas et al 2017).…”
Section: Models and Data Used In Inverse-modeling Approachesmentioning
confidence: 99%
“…Esta interacción está determinada, en parte, por las condiciones del clima, el agua en la superficie y las características del medio granular superficial. El análisis y predicción del comportamiento de dicha interacción, está controlado principalmente por propiedades del suelo como la textura, estratigrafía, propiedades hidráulicas, contenidos de humedad y materia orgánica, incluidos diferentes aspectos de migración de solutos (Kung, 1990;Rudolph et al, 1996;Yazaki et al, 2006;McMahon et al, 2006;Segal et al, 2008;Thomas et al, 2017). Recientemente, el estudio del comportamiento del ciclo del agua en la zona no saturada se orienta a la predicción de los efectos del cambio climático y sus impactos en el agua subterránea, producción de alimentos y permanencia de ecosistemas (Maxwell y Kollet, 2008;Bell et al, 2010;Heinlein et al, 2017).…”
Section: Introductionunclassified